A balanced dual‐band BPF with independently controllable frequencies and bandwidths. Issue 6 (15th March 2019) - Chen, Lei; Gan, Yan Ni; Wei, Feng; Zou, Xin Tong; Xiao, Qin Kun
Abstract: A balanced second‐order dual‐band bandpass filter (BPF) with independently controllable center frequencies and bandwidths based on coupled stepped‐impedance resonators (SIRs) is designed in this article. To obtain a dual‐band differential‐mode (DM) response, two pairs of SIRs with different resonant frequencies are employed in the design. The bandwidths of the two DM passbands can be independently tuned by adjusting the coupling gaps and coupling lengths of the corresponding resonators. In addition, three transmission zeros are realized to enhance the selectivity of the DM passbands. The microstrip‐slotline transition structure is utilized to achieve a wideband common‐mode (CM) suppression. Moreover, the DM responses are independent of the CM ones, which significantly simplify the design procedure. Finally, a balanced dual‐band BPF is designed to validate the design method and a good agreement between the simulated and measured results is observed.